Opacities of singly and doubly ionised neodymium and uranium for kilonova emission modeling - Flörs, A. (2023)
ACKNOWLEDGEMENTS AF, GL, LJS and GMP acknowledge support by the European Research Council (ERC) under the State of Hesse within the Cluster Project ELEMENTS. JD and SG acknowledge financial support from F.R.S.-FNRS (Belgium). RFS, JMS, JPM and PA acknowledge the support from FCT (Portugal) through research center funding UID/04559/2020 (LIBPhys). PQ is Research Director of the F.R.S.- FNRS. HCG is a holder of a FRIA fellowship. PP is a Research Associate of the Belgian Fund for Scientific Research F.R.S.-FNRS. This work has been supported by the Fonds de la Recherche Scientifique (FNRS, Belgium) and the Research Foundation Flanders (FWO, Belgium) under the Excellence of Science (EOS) Project (number O022818F and O000422F). Computational resources have been provided by the Consortium des Equipements de Calcul Intensif (CECI), funded by the F.R.S.-FNRS under Grant No. 2.5020.11 and by the Walloon Region of Belgium. We thank G. Gaigalas, M. Tanaka, D. Kato and C. J. Fontes for making some or all of their calculated atomic data public, facilitating benchmarks with other codes